Note on the suitability of rubber wood(Hevea brasiliensis) for handicrafts - Rao P V K; Kamala B S; Srinivasan V V (Journal of the Timber Development Association(India), 1993)
From the point of view of economic value of rubber tree, the end utilisation of wood after its complete tapping of latex plays a significant role. The wood which was mainly used for packing cases and firewood has now been found suitable for many wood industries including furniture making. The only set back is the presence of 15;to 65;tension wood in the same plank more frequently, thus restricting big sized plank for use as load bearing members. The study in this paper highlights the potential value of the rubberwood which could replace many wood species used in handicraft after lacquering. Another special feature of the rubberwood is its workable surface that could be brought out on the articles using its grain and minor defects like knots etc. These surfaces with plain polish or colourless lac increases the value of the article.
Keywords: Handicrafts; Rubberwood